Comparing Writing Outcomes in Online and In-Person EFL Instructions for Intermediate Male and Female Students - Leyla Moghimi; Sina Mirzaei (International Journal of Practical and Pedagogical Issues in English Education)
This study investigates the effectiveness of online versus in-person classes in enhancing English as a Foreign Language (EFL) writing skills among Iranian learners. Utilizing a quasi-experimental design, the research involved eighty-four intermediate-level students from Jahad-e-Daneshgahi Language Institute in Urmia, Iran. Employing various instruments, including the PET Test, Effective Academic Writing 2, and pre/posttests, the study compared learners' writing performance across both learning environments. The analysis, primarily using ANOVA, revealed that online classes significantly improved writing proficiency compared to traditional in-person instruction, with no gender-based differences in performance noted in either environment. These findings offer insights for educators and curriculum designers in developing strategies to enhance EFL learners' writing skills. The results also suggest the importance of further research into the mechanisms through which online environments affect learning outcomes, potentially guiding the development of more effective EFL instructional practices. This contribution is particularly relevant for the ongoing refinement of teaching methodologies in the digital age, emphasizing the role of empirical evidence in shaping educational approaches.